2013
DOI: 10.1007/s13277-013-0734-y
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in K-ras, APC and p53-multiple genetic pathway in colorectal cancer among Indians

Abstract: The incidence of colorectal cancer (CRC) is increasing rapidly in Asian countries during the past few decades, but no comprehensive analysis has been done to find out the exact cause of this disease. In this study, we investigated the frequencies of mutations and expression pattern of K-ras, APC (adenomatosis polyposis coli) and p53 in tumor, adjoining and distant normal mucosa and to correlate these alterations with patients clinicopathological parameters as well as with the survival. Polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 49 publications
5
22
0
1
Order By: Relevance
“…COAD in cluster_V had better outcome compared to COAD located in other clusters (Fig. 3g) ( n =334), which may, in part, be due to depletion of mutations in TP53 (6% vs. 15%, Fisher’s Exact (FE) P = 0.05), APC (14% vs. 25%, FE P = 0.044) and KRAS (5% vs. 16%, FE P = 0.013), consistent with previous literature showing these are associated with a worse outcome 30, 31, 32 . The poor outcome for KIRC in cluster_VII may be partly due to enrichment of TP53 mutations (6% vs. 0.8%, FE P = 0.005, n =454) (Fig.…”
Section: Resultssupporting
confidence: 86%
“…COAD in cluster_V had better outcome compared to COAD located in other clusters (Fig. 3g) ( n =334), which may, in part, be due to depletion of mutations in TP53 (6% vs. 15%, Fisher’s Exact (FE) P = 0.05), APC (14% vs. 25%, FE P = 0.044) and KRAS (5% vs. 16%, FE P = 0.013), consistent with previous literature showing these are associated with a worse outcome 30, 31, 32 . The poor outcome for KIRC in cluster_VII may be partly due to enrichment of TP53 mutations (6% vs. 0.8%, FE P = 0.005, n =454) (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Similar to the present data, Iwamoto et al (47) reported loss of APC expression in 83% of colon cancers. However, recently, Malhotra et al reported in Indian patients that 63% of tumor tissue expressed APC with low intensity, and in adjoining mucosa, 80% of tumor tissue expressed APC protein (48). Furthermore, correlation of APC mutation pattern with the protein expression was also analyzed but no association was found, which is in line with a previous study (48).…”
Section: Discussionsupporting
confidence: 73%
“…However, recently, Malhotra et al reported in Indian patients that 63% of tumor tissue expressed APC with low intensity, and in adjoining mucosa, 80% of tumor tissue expressed APC protein (48). Furthermore, correlation of APC mutation pattern with the protein expression was also analyzed but no association was found, which is in line with a previous study (48). This can be attributed to the fact that the loss of APC protein is not only due to mutations but also to the aberrant methylation of CpG islands in the promoter region of APC as previously demonstrated (15).…”
Section: Discussionmentioning
confidence: 99%
“…The initiating events for the majority of CRCs are mutations in the APC, resulting in increased levels of β-catenin, followed by mutations in K-ras and in p53 [29]. However, in a cohort of CRC patients, only 3.3 % of tumors contained the combination of these three gene mutations, suggesting that these mutations may lie on alternative pathways of tumor development in CRC [30]. RT is a common treatment for advanced rectal cancer and is a great benefit to many patients because it reduces the risk of local recurrence.…”
Section: Discussionmentioning
confidence: 99%